Rattus hainaldi Kitchener, How & Maharadatunkamsi 1991 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
696. Hainald’s Flores Island Rat Rattus hainaldi French: Rat de Hainald / German: Hainald-Ratte / Spanish: Rata de Flores de Hainald Other common names: Hainald's Rat Taxonomy. Rattus hainaldi Kitchener, How & Maharadatunkamsi, 1991, Desa [Longko, 8 km SSE Ruteng, above Kampong Robo, 1300 m, Gunung Ranakah, Pulau Flores, Nusa Tenggara, Indonesia. This species is monotypic. Distribution. Flores I, Indonesia. Descriptive notes. Head-body 133 mm, tail 161 mm, ear 21 mm, hindfoot 29 mm; weight 81 g. Hainald’s Flores Island Rat has a smallbody; very long tail relative to head-body length, with bicolored pattern including whitish undersurface; orange brown dorsal pelage, speckled with dark brown; creamy white venter; chest posteriorly flecked with pale gray; and soft pelage, with long guard hairs on flanks and dorsum. Skull is small, with small incisive foramina; medium-sized bulla; low temporal and postorbital ridges; and short rostrum that is relatively broad compared with skull length. Habitat. Primary and ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 842, DOI: 10.5281/zenodo.6887260 ...